(untitled) (Medico Legal Update, 2019)
Road construction is viewed as a core development activity.The unfortunate downside of this is the increasing burden of Road traffic Injuries(RTIs). 50 years ago, the WHO was called upon to do something about the heavy human toll of RTIs. However, RTIs remain a very significant contributor to human morbidity and mortality. It is significant to note that the burden of RTIs has shifted to low and middle income countries (LMICs), which despite having only about 50% of the world’s motor vehicles, account for 90% of the burden of 12.5 lakh road traffic deaths and 2 to 5 crore non fatal road traffic injuries. UN Sustainable development goal (SDG) target 3.6 is to reduce by 50% the number of deaths and injuries from road traffic crashes across the globe by 2020.This implies the saving of 50 lakh lives,the prevention of 5 crore serious injuries, and an economic benefit to the tune of over US3 trillion.This is a major challenge. The WHO says that RTIs have a significant negative macroeconomic impact in LMICs.The loss to national GDP ranges from 1.03 percent in South Korea to 2.9 percent in Vietnam.Reducing RTI morbidity and mortality by 50% over a 24 year timeline can generate an additional flow of income equivalent to 22.2 % GDP(2014) in Thailand, 15% in China, 14% in India,7.2% in the Philippines and 7.1% in Tanzania. RTI deaths in India have consistently increased year on year from 1990 to 2015.